Exploring the Relationship between Breastfeeding Practices and Acute Otitis Media Incidence in Children: Mechanisms and Implications - Syamsurizal , Zein; Anggreyni, Olivia (International Journal on Health and Medical Sciences, 2024)
Acute Otitis Media (AOM) represents a common childhood ailment with significant implications for pediatric health. While breastfeeding has long been purported to confer protection against AOM, the precise nature of this relationship and underlying mechanisms remain incompletely understood. This research aimed to elucidate the relationship between breastfeeding practices and AOM incidence in children, as well as to explore potential mechanisms underlying this association. A comprehensive review of existing literature was conducted, encompassing systematic reviews, meta-analyses, longitudinal cohort studies, and mechanistic investigations. Studies investigating the incidence of AOM in relation to breastfeeding practices, as well as mechanistic pathways such as maternal antibodies, antimicrobial factors, anti-inflammatory properties, and microbiota modulation, were synthesized to provide a comprehensive understanding of the topic. The synthesis of existing evidence revealed a consistent and robust association between breastfeeding practices and reduced AOM incidence in children. Meta-analyses demonstrated a lower AOM risk among breastfed infants compared to non-breastfed counterparts, with exclusive breastfeeding yielding the greatest risk reduction. Longitudinal cohort studies further elucidated a dose-response relationship between breastfeeding duration and AOM risk, underscoring the protective effect of prolonged breastfeeding. Mechanistic investigations highlighted the role of maternal antibodies, antimicrobial factors, anti-inflammatory properties, and microbiota modulation in mediating breastfeeding's protective effect against AOM.